The relationship between FDI quality, new quality productivity forces, and economic resilience in China’s Yangtze River Delta region: insights from an empirical spatial Durbin model - Haiping Lv; Yi Lian; Xiangyu Hua (Humanities & Social Sciences Communications)
Abstract In the context of increasing natural disasters, volatile geopolitical dynamics, and rising anti-globalization trends—particularly in the post-pandemic era—enhancing economic resilience has become crucial. This study investigates how FDI quality and new quality productivity forces influence economic resilience across 41 cities in China’s Yangtze River Delta (2009–2022). We establish measurement systems for FDI quality, new quality productivity forces, and economic resilience, conducting empirical analyses across temporal and spatial dimensions. Three main findings emerge: First, significant spatial disparities exist, with eastern/northern regions outperforming western/southern areas in all three dimensions. While new quality productivity forces and resilience show upward trends with fluctuations, FDI quality exhibits stagnation and regional imbalances. Second, temporal analysis reveals a U-shaped relationship where FDI quality affects both new quality productivity forces and resilience, with new quality productivity forces demonstrating significant mediation effects. Third, spatial econometric results show an inverted U-shaped spillover effect of FDI quality on neighboring regions’ resilience. These findings provide empirical evidence on the mechanisms through which external investments (FDI) and internal innovation capabilities (new quality productivity forces) jointly shape regional economic resilience, offering valuable insights for policymakers to address development disparities and enhance risk resistance capacities in the new era.